2013
DOI: 10.1016/j.resp.2013.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Variability of respiratory mechanics during sleep in overweight and obese subjects with and without asthma

Abstract: Variability of respiration may provide information regarding disease states. We sought to characterize variability of ventilation and resistance in healthy and asthma, to determine how respiratory control may be altered in sleep and with bi-level positive airway pressure (BPAP). Overweight and obese subjects with and without asthma were studied during sleep at baseline and with BPAP, while measuring respiratory system resistance (Rrs) continuously. Stable periods (>20min) of wake, NREM, and REM sleep were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Other physiological parameters that were identified as being useful included measurements of heart rate, respiratory rate and sleep quality. Given that heart rate variability may be associated with asthma control [24], that respiratory rate variability during sleep may differ between individuals with and without asthma [25], and that nocturnal wakening is a common complaint of individuals with asthma, the potential for these measurements to provide support for asthma self-management warrants further investigation. Each year 5.5 million deaths can be attributed to poor air quality [26], whilst air pollution exposure is associated with increased frequency of asthma attacks in children and adults [27].…”
Section: Discussionmentioning
confidence: 99%
“…Other physiological parameters that were identified as being useful included measurements of heart rate, respiratory rate and sleep quality. Given that heart rate variability may be associated with asthma control [24], that respiratory rate variability during sleep may differ between individuals with and without asthma [25], and that nocturnal wakening is a common complaint of individuals with asthma, the potential for these measurements to provide support for asthma self-management warrants further investigation. Each year 5.5 million deaths can be attributed to poor air quality [26], whilst air pollution exposure is associated with increased frequency of asthma attacks in children and adults [27].…”
Section: Discussionmentioning
confidence: 99%
“…Even though several studies investigated the correlation properties of breathing pattern[ 2 5 , 7 ], only few addressed the correlation properties of EEV such as functional residual capacity (FRC) in humans, likely because of the difficulties in continuous monitoring. To our knowledge, the only study addressing this issue is by Hlastala et al [ 19 ], in which the authors used a complicated set-up based on total body plethysmography in supine position to record FRC fluctuations and other respiratory parameters in four healthy subjects for 40 min.…”
Section: Discussionmentioning
confidence: 99%
“…There are several possible reasons for the difference. For example, correlation properties of V T and T i have been shown to depend on sleep stage [ 5 ]. Additionally, the α of respiratory resistance at 8 Hz in human subjects decreased from wake to sleep [ 5 ] suggesting less active brain control of respiratory variables during sleep.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Previous research showed that variability of RR during sleep is different in asthmatics. 48 Additionally, an increased resting RR during the day might also indicate loss of asthma control. Therefore, continuous analysis of RR during the day and while sleeping might prove useful in the prediction of asthma control.…”
Section: Discussionmentioning
confidence: 99%